Using green finance to promote global growth in a sustainable way. (6th February 2023) - Taneja, Sanjay; Kaur, Simranjeet; Özen, Ercan
Green finance is gaining traction as a public policy objective. This paper summarises global and Indian progress in the field of green finance. Also, it examined the development in the field of the green finance in India, roadmap of the green finance sustainability, requirement for the significance of the green finance and Initiatives taken by the Government of India. Using a variety of data sources, we analyse public awareness (Google Trends) and financial possibilities (bank loans and bond issuances) for green initiatives. While public awareness and financing options have improved in India, our findings indicate that reducing asymmetric information through improved information management systems and increased collaboration among stakeholders could pave the way for more environmentally friendly and sustainable long-term economic growth. The need for the supply of sustainable financing to grow faster, already demonstrated by the financial gap for the sustainable development goals, has been reinforced from post-COVID19 environment, with escalation of climate issue. For this, investors, investees, middlemen and policymakers must discover methods to collaborate more effectively and with a greater sense of urgency.